Activation of NF-kappaB by the intracellular expression of NF-kappaB-inducing kinase acts as a powerful vaccine adjuvant. - Andreakos, E; Williams, R; Wales, J; Foxwell, B; Feldmann, M (2006)
There is a pressing need for adjuvants that will enhance the effectiveness of genetic vaccines. This is particularly important in cancer and infectious disease such as HIV and malaria for which successful vaccines are desperately needed. Here, we describe an approach to enhance immunogenicity that involves the activation of NF-kappaB by the transgenic expression of an intracellular signaling molecule, NF-kappaB-inducing kinase (NIK). In vitro, NIK increases dendritic cell antigen presentation in allogeneic and antigen-specific T cell proliferation assays by potently activating NF-kappaB and consequently up-regulating the expression of cytokines (TNF-alpha, IL-6, IL-12, IL-15, and IL-18), chemokines [IL-8, RANTES (regulated on activation, normal T cell expressed and secreted), macrophage inflammatory protein-1alpha, monocyte chemoattractant protein-1, and monocyte chemoattractant protein-3], MHC antigen-presenting molecules (class I and II), and costimulatory molecules (CD80 and CD86). In vivo, NIK enhances immune responses against a vector-encoded antigen and shifts them toward a T helper 1 immune response with increased IgG2a levels, T cell proliferation, IFN-gamma production, and cytotoxic T lymphocyte responses more potently than complete Freund's adjuvant, a very efficacious T helper 1-inducing adjuvant. These findings define NIK, and possibly other inducers of NF-kappaB activation, as a potent adjuvant strategy that offers great potential for genetic vaccine development.